2017
DOI: 10.1108/jmp-05-2016-0146
|View full text |Cite
|
Sign up to set email alerts
|

Influence of event characteristics on assessing credibility and advice-taking

Abstract: Purpose The purpose of this paper is to examine how the environment surrounding a decision-making event affects whether decision-makers consider the credibility of their advisors and take their advice. Design/methodology/approach In two experiments, the characteristics of the event and credibility of the advisor were manipulated, the extent to which participants considered the information from the advisor was measured, and whether participants took advice was determined. Findings Decision-makers are more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Gigone & Hastie, 1993;Hartmann & Rad, 2017;Reutlinger, 2016). Apart from correlational evidence for the dependence of advice taking on credibility (Johnson & Johnson, 2017;Tenney, Spellman, & MacCoun, 2008), hardly any prior research (with the notable exception of Schultze, Mojzisch, & Schulz-Hardt, 2017) has addressed the ability to evade invalid advice.…”
Section: Introductionmentioning
confidence: 99%
“…Gigone & Hastie, 1993;Hartmann & Rad, 2017;Reutlinger, 2016). Apart from correlational evidence for the dependence of advice taking on credibility (Johnson & Johnson, 2017;Tenney, Spellman, & MacCoun, 2008), hardly any prior research (with the notable exception of Schultze, Mojzisch, & Schulz-Hardt, 2017) has addressed the ability to evade invalid advice.…”
Section: Introductionmentioning
confidence: 99%
“…The other theme that has been rejected in model testing is the evaluation approach, which refers to management tendency to use intra or extra advisors in performance evaluations. As Jhonson and Jhonson (2017, p. 99) maintained, “Under low-urgency or high-criticality conditions, decision-makers distinguish the credibility of their advisors in deciding whether to follow their advice. When conditions are highly urgent or not critical, decision-makers ignore cues of advisors” credibility and therefore their advice, even if it is from high credibility advisors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tilcsik and Marquis (2013) reported that natural disaster events with severe damage reduce the willingness of corporate philanthropy, whereas lowstrength events can promote corporate philanthropy. Johnson and Johnson (2017) indicated that a smaller urgency and higher criticality of an organizational event corresponded to a higher likeliness of the decision-maker to implement advice-taking behaviour. Moreover, Moghavvemi et al, who examined the adoption of information technology (IT) innovation, highlighted that high-strength external events, such as financial crises and market changes, could prompt IT entrepreneurs to consider feasible alternatives to better survive in the market, thereby enhancing the probability of adopting innovative technologies (Moghavvemi et al 2015(Moghavvemi et al , 2016.…”
Section: Theoretical Basis and Research Hypothesesmentioning
confidence: 99%